2016
DOI: 10.1016/j.optmat.2016.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced single-particle brightness and photostability of semiconductor polymer dots by enzymatic oxygen scavenging system

Abstract: Semiconductor polymer dots (Pdots) are emerging as an excellent fluorescent probe in biology and medicine. However, the photostability of Pdots can't meet the requirements of long term single-particle imaging and tracking applications. Here we describe the enhanced single-particle brightness and photostability of Pdots by using an efficient enzymatic oxygen scavenging system (OSS). Pdots with particle diameters of 21 nm and 43 nm (PFBT21 and PFBT43) were prepared by a nanoprecipitation method. Single-particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…These observations are attributed to the presence of non-emissive exciton quenching sites or recombination centers (Q). , The number, nature, and location of Q centers appear to be highly dependent on several parameters associated with CPN preparation conditions. For example, the fluorescence lifetime (τ 0 CPN ) and quantum yield (Φ F0 CPN ) of our F8BT CPNs in the absence of dyes are different from those reported by some authors but matches those reported by other authors. , The nature of Q sites has been associated with a number of entities such as polymer synthesis defects and charged species such as hole/electron–polarons. In particular, there are a significant number of publications describing efficient exciton quenching by charged species (polarons).…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…These observations are attributed to the presence of non-emissive exciton quenching sites or recombination centers (Q). , The number, nature, and location of Q centers appear to be highly dependent on several parameters associated with CPN preparation conditions. For example, the fluorescence lifetime (τ 0 CPN ) and quantum yield (Φ F0 CPN ) of our F8BT CPNs in the absence of dyes are different from those reported by some authors but matches those reported by other authors. , The nature of Q sites has been associated with a number of entities such as polymer synthesis defects and charged species such as hole/electron–polarons. In particular, there are a significant number of publications describing efficient exciton quenching by charged species (polarons).…”
Section: Resultscontrasting
confidence: 73%
“…For example, the fluorescence lifetime (τ 0 CPN ) and quantum yield (Φ F0 CPN ) of our F8BT CPNs in the absence of dyes are different from those reported by some authors 33−35 but matches those reported by other authors. 36,37 The nature of Q sites has been associated with a number of entities such as polymer synthesis defects and charged species such as hole/electron−polarons. In particular, there are a significant number of publications describing efficient exciton quenching by charged species (polarons).…”
Section: Resultsmentioning
confidence: 99%
“…NIRabsorbing SPNs have emerged as a new class of photonic nanoagents for molecular imaging. 73,97,[135][136][137][138][139][140][141][142] By virtue of the high photostability and ROS resistance, SPNs were developed into activatable PA probes for imaging of ROS both in vitro and in vivo. 71 Poly(cyclopentadithiophene-alt-benzothiadiazole) (SP1) was transformed into the nanoprobe by co-precipitation with a ROS-sensitive NIR dye (IR775S) and lipid (Figure 6a).…”
Section: Rosmentioning
confidence: 99%
“…ROS is a hallmark of many pathological processes ranging from acute and chronic bacterial infections to chronic diseases such as cancer, cardiovascular disease, and arthritis. ,, Imaging of ROS in living animals is challenging because many photonic imaging agents such as small-molecule dyes, QDs, and gold nanoparticles are not stable in the presence of ROS. NIR-absorbing SPNs have emerged as a new class of photonic nanoagents for molecular imaging. ,, By virtue of the high photostability and ROS resistance, SPNs were developed into activatable PA probes for imaging of ROS both in vitro and in vivo . Poly­(cyclopentadithiophene- alt -benzothiadiazole) (SP1) was transformed into the nanoprobe by coprecipitation with a ROS-sensitive NIR dye (IR775S) and lipid (Figure a).…”
Section: Design and Applications Of Activatable Pa Probesmentioning
confidence: 99%
“…In recent years, semiconductor polymer dots (Pdots) as a kind of new luminescent nanomaterial have been widely used in biosensing, , in vivo imaging, , drug and gene delivery, , single particle tracing, , and super-resolution imaging . Pdots exhibit excellent optical properties, including extraordinary fluorescence brightness, ultrafast emission rate, and good photostability.…”
mentioning
confidence: 99%